Bis(pyridine)iodonium Tetrafluoroborate (IPy2BF4): a versatile oxidizing reagent - Barluenga, José (2004)
The use of bis(pyridine)iodonium tetrafluoroborate (IPy2BF4) as an oxidizing agent towards different types of alcohols is reported. The observed reactivity involves different reaction pathways, as a function both of the structures of the starting materials and of the experimental conditions. Interestingly, the title iodine-containing compound is capable of a tuneable reaction with simple cycloalkanols, providing straight and selective access either to ω-iodocarbonyl compounds or to ketones, a previously unreported and chemoselective range of oxidation potential. Furthermore, appropriate conditions for the preparation of aldehydes and esters from primary alcohols by easily performed experimental procedures were also established. The β-scission reactions of cycloalkanols and the α-oxidation processes of primary, secondary and benzylic alcohols are discussed.